An analysis of the potential socio-economic impacts of shale gas development in South Africa - Tukwayo, Yonela (Research of GSB, 2017)
The South African government is in the process of considering shale gas exploration applications in the Karoo basin. There are conflicting views on whether the development of the resource will be to the detriment or benefit of the South African economy. This paper makes use of a dynamic Computable General Equilibrium (CGE) model adapted for the South African energy sector to analyse the potential socio-economic impacts of the development of shale gas. Simulation results indicate potential negative impacts on GDP contribution by all the sectors simulated, except the natural gas sector and the Gas-to-Liquid petroleum sector, as well as potential negative impacts on employment. The negative impacts on growth and employment are likely to worsen poverty and inequality. Potential impacts on trade are negative as the trade deficit increases. In terms of environmental impacts, the uptake of gas would decrease CO2 emissions. All results are compared to the baseline scenario. Based on these results, it is recommended that the decision on whether the development should go ahead or not ought to take into account the potential socio-economic costs, and potential ways to hedge against them.